Prototyping decentralized electronic blockchain voting system - Горбенко, І.Д.; Кузнецов, О.О.; Полуяненко, М.О.; Кіян, А.С.; Лисицький, К.Є.; Кандій, С.О. (Radiotekhnika, 2020)
The modern electronic voting system is an interconnected set of rules, methods, processes, tools and technologies, as well as legal norms that ensure and regulate the remote legitimate will of authorized users (voters). This article proposes, investigates, and verifies by physical prototyping the two-tier architecture of the electronic blockchain voting system. The lower (first) level enables all components of the electronic identification process to be fulfilled by existing systems such as BankID, MobileID, electronic signature, and the like. This will ensure interoperability of electronic voting, inheritance of already implemented national information systems, in particular, of the national system of electronic confidential services, reproducibility of the results of physical prototyping of blockchain voting. The upper (second) level is intended for the implementation of the expression of votes and the counting of votes, with the provision of independent control over the correctness of the compilation of voter lists; the possibility of anonymous voting only by those who are entitled to it; the invariability and irrevocability of the results of the will; ease and transparency of checking the correctness of the vote count and the like. The obtained results of physical prototyping make it possible to confirm the validity and weight of the developed architecture, its ability to meet the basic requirements of decentralized electronic voting, the requirements of information and functional security and reliability of information technologies. The practical implementation of the developed blockchain voting architecture will increase trust in information resources and services (which is especially relevant for government agencies) and will reduce time and overhead; will make impossible the intervention of centralized institutions and possible corruption; will increase the reliability of information storage and the quality of services provided.